SIRT3-AMPK signaling pathway as a protective target in endothelial dysfunction of early sepsis - Yu, Huilin; Liu, Qian; Chen, Guodong; Huang, Longxiang; Luo, Minghao; Lv, Dingyi; Luo, Suxin (International immunopharmacology, 2022)
•We demonstrated that p-AMPK expression in the aorta increased in the early stage of sepsis.•Activation of AMPK protected the vascular endothelial function and improved survival in septic mice.•SIRT3 activated AMPK to counteract the role of NF-κB and NLRP3 pathways in the early stage of sepsis. Extensive vascular endothelial dysfunction usually occurs in sepsis, resulting in high mortality. The purpose of this study was therefore to investigate the role of AMP-dependent protein kinase (AMPK) in the aortic endothelial dysfunction of early sepsis in mice, and the relationship between AMPK and Sirtuin3 (SIRT3). Cecal ligation and puncture (CLP) surgery was performed to establish a mouse sepsis model, and human umbilical vein endothelial cells (HUVECs) were treated with lipopolysaccharide (LPS) to mimic a sepsis model in vitro. We suppressed and increased the activities of AMPK with Dorsomorphin (CC) and Acadesine (AICAR), respectively. 3-TYP (SIRT3 inhibitor) and Honokiol (SIRT3 agonist) were used to alter SIRT3 activity. Then, the inflammatory and endothelial function parameters of the vascular tissue and survival rate were determined. In vivo, the expression of Ser1177 phosphorylation of endothelial nitric oxide synthase (p-eNOS), endothelium-dependent relaxation function, and survival decreased (P < 0.05), while NF-κB and NLRP3 pathways were activated in CLP-induced early sepsis (P < 0.05). Moreover, activation of AMPK significantly reversed the reduction of p-eNOS expression (P < 0.05), prevented endothelial dysfunction (P < 0.05), deactivated NF-κB and NLRP3 pathways (P < 0.05), and improved survival (P < 0.05) in septic mice. However, AMPK inhibition led to opposite effects (P < 0.05). In addition, changing the activity of AMPK had little effect on SIRT3 expression (P > 0.05), while the expression of p-AMPK varied with the inhibition or activation of SIRT3 (P < 0.05), which was further demonstrated using in vitro experiments. Together, the results showed that the SIRT3-AMPK signaling pathway played an important role in inhibiting vascular inflammation and endothelial dysfunction during early sepsis.